Diversidade e inclusão: um estudo sobre gênero em uma indústria farmacêutica - Soranz, Rossana Filetti (2009)
The diversity plays an increasingly important role within organizations, sometimes due to social justice reasons, or for reaching greater organizational efficiency and effectiveness. However, having a demographically and heterogeneous staff does not mean necessarily that its components feel included in the work environment. The aim of this study was to investigate the relationship between the experience of inclusion and the working group, individual and organizational policies and practicies inclusive behavior, of women working in a pharmaceutical industry. The research was carried out according to a quantitative method with 60 questions. It was reached a total of 330 valid respondents. The results show the inclusion experience is more positively related to the working group inclusion behavior, followed by the individual inclusion behavior and then the organization ones. Furthermore, for women, the behavior of inclusion generates less experience of inclusion than for men, and the fact that women work in various working groups on gender is not positively associated to the behavior and the experience to include them.